2008
DOI: 10.1371/journal.pbio.0060150
|View full text |Cite
|
Sign up to set email alerts
|

Group II Intron Protein Localization and Insertion Sites Are Affected by Polyphosphate

Abstract: Mobile group II introns consist of a catalytic intron RNA and an intron-encoded protein with reverse transcriptase activity, which act together in a ribonucleoprotein particle to promote DNA integration during intron mobility. Previously, we found that the Lactococcus lactis Ll.LtrB intron-encoded protein (LtrA) expressed alone or with the intron RNA to form ribonucleoprotein particles localizes to bacterial cellular poles, potentially accounting for the intron's preferential insertion in the oriC and ter regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Suppression suggests that the effect of ppGpp is mediated via RNA polymerase. Although not all ppGpp mutants depress retromobility, possibly due to the different host strains and assay systems used, the above studies provide a satisfying correspondence of regulatory effects mediated via phosphate metabolism and suggest that nutritional stress may be an activator of group II intron mobility (48,210).…”
Section: Group II Intronsmentioning
confidence: 98%
See 1 more Smart Citation
“…Suppression suggests that the effect of ppGpp is mediated via RNA polymerase. Although not all ppGpp mutants depress retromobility, possibly due to the different host strains and assay systems used, the above studies provide a satisfying correspondence of regulatory effects mediated via phosphate metabolism and suggest that nutritional stress may be an activator of group II intron mobility (48,210).…”
Section: Group II Intronsmentioning
confidence: 98%
“…Small molecules: polyphosphates, (p)ppGpp and cAMP-Recent work has identified five genes in E. coli, gppA, uhpT, wcaK, ynbC, and zntR, whose disruption leads to a more diffuse cellular distribution of the IEP, accompanied by a more uniform distribution of intron integrations around the genome (210). The common factor in these mutants is accumulation of intracellular polyphosphate, which was also shown to bind to LtrA and to alter distribution of other pole-localized basic proteins.…”
Section: Group II Intronsmentioning
confidence: 99%
“…As expected, pathways using nascent DNA strands as primers are favored under rapid growth conditions, which lead to an increased frequency of replication forks (Coros et al 2005). Retromobility of the Ll.LtrB intron is also influenced in interesting ways by cellular interactions, host factors, and stress responses (Beauregard et al 2008;Zhao et al 2008;Coros et al 2009). …”
Section: Group II Intronsmentioning
confidence: 99%
“…These studies also gave the first hint that culture conditions can regulate retrotransposition, as slow growth eliminated all events except those around ori and ter and confined them to an endonucleasedependent pathway into dsDNA (59). Additionally, a mutagenesis screen showed that Ll.LtrB IEP localization is related to its interaction with negatively charged intracellular polyphosphates, which are normally polelocalized but delocalize away from the poles in response to cellular stress, leading to a more uniform distribution of intron-insertion sites (96). These studies portended growth phase and cellular stress as regulatory forces in retrotransposition.…”
Section: Mechanism and Regulation Of Group II Intron Retrotranspositionmentioning
confidence: 99%